Study protocol: MRI-based assessment of cerebral blood flow under pharmacologically elevated blood pressure in patients under general anesthesia, and in sedated ICU patients with aneurysmal subarachnoid hemorrhage - Jonas Österlind; Johan Birnefeld; Elin Birnefeld; Magnus Hultin; Sara Qvarlander; Anders Wåhlin; Petter Holmlund; Laleh Zarrinkoob (PLoS ONE, 2025)
Background Maintaining cerebral perfusion during anesthesia and intensive care is critical, yet the relationship between mean arterial pressure (MAP) and cerebral blood flow (CBF) remains poorly defined. In patients with aneurysmal subarachnoid hemorrhage (aSAH), pharmacologically induced hypertension is commonly applied to support cerebral perfusion, but its effects are uncertain. Methods This protocol describes two parallel clinical studies using identical methodology. The first study population includes adults undergoing elective general anesthesia (MAP-ANE), and the second comprises sedated intensive care patients with aSAH (MAP-SAH). In both study populations, MAP will be increased stepwise with norepinephrine (NE) infusion under continuous invasive blood pressure monitoring, and CBF measured with phase-contrast MRI (PCMRI) and arterial spin labeling (ASL), while near-infrared spectroscopy (NIRS) will be performed in parallel to evaluate its validity as a surrogate marker. The primary outcome is the change in total CBF between baseline and elevated MAP, directly testing whether induced hypertension increases CBF. Secondary outcomes include ASL perfusion changes, the slope of the MAP–CBF relationship, systemic–cerebral hemodynamic correlations, and NIRS responses. Expected impact These studies test the hypothesis that pharmacological MAP augmentation does not predictably increase CBF. By combining quantitative MRI with invasive monitoring, it aims to clarify MAP–CBF interactions, define the physiological basis of induced hypertension, and assess whether NIRS can serve as a clinically useful proxy. Findings are expected to inform safer and more individualized blood pressure management in perioperative and neurocritical care. The studies are registered at ClinicalTrials.gov (MAP-ANE: NCT06855407; MAP-SAH: NCT06033378). Trial registration ClinicalTrials.gov, MAP-ANE NCT06855407 , MAP-SAH NCT06033378